Keabsahan Akad Nikah Virtual dalam Pandangan Empat Mazhab - Luthfiatul Zahra; Diah Cahyani; Abdul Sani; Fadullah Rusadi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of information and communication technology has brought significant changes to various aspects of human life, including marriage practices. The implementation of marriage contracts conducted through online media such as video calls or digital conferencing platforms has emerged as a modern phenomenon. This development has sparked legal debates in Islam regarding its validity, particularly concerning the fulfillment of essential conditions and pillars of marriage, such as ittihād al-majlis (unity of the session) and the sighat ijab qabul (offer and acceptance). The purpose of this article is to examine the validity of virtual mge contracts from the perspective of the four major schools of Islamic jurisprudence (Hanafi, Maliki, Shafi'i, and Hanbali). This study employs a qualitative research methodology using a literature review with a descriptive-analytical approach. The findings indicate that the Shafi'i School does not permit virtual marriage contracts due to the absence of physical unity in place. In contrast, the Hanafi, Maliki, and Hanbali Schools allow virtual marriage contracts, emphasizing unity in time and clarity in the sighat. Therefore, according to several schools of Islamic jurisprudence, virtual marriage contracts may be considered valid as long as the required conditions of marriage are fulfilled, including the presence of witnesses and the clarity of the ijab qabul.